The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00068-016-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

Marginal ulcer perforation: a single center experience

Abstract: MUP patients do not present with septic shock. Omental patch repair or primary closure is sufficient enough. Revision of Billroth-II-GJ into Roux-en-Y-GJ is not mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Quantifying the cross-country inequalities in the burden of PUD across the SDI increases understanding of its determinants and identifies countries that must strengthen PUD prevention and control. 14,15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying the cross-country inequalities in the burden of PUD across the SDI increases understanding of its determinants and identifies countries that must strengthen PUD prevention and control. 14,15…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying the cross-country inequalities in the burden of PUD across the SDI increases understanding of its determinants and identifies countries that must strengthen PUD prevention and control. 14,15 In this study, we comprehensively analyzed the disease burden (incidence, DALYs, mortality) of PUD at the global, regional, and national levels with their corresponding current trends and survival patterns from 1990 to 2019. In general, the incidence cases of PUD have been increasing since 1990, reaching 3.6 million in 2019; however, the ASIR showed a continuous downward trend, with an average annual decrease of 1.42%; we conjectured this attributable to the population growth and worldwide aging, popularity of upper endoscopy, improvement of medical sanitary, PUD has declined significantly from 1990 to 2019 in the point of ASIR, ASDR, and ASMR, decreasing by a mean of 1.42%, 3.47%, and 3.36%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Marginal ulcer, an ulcer at the margins of the gastro-jejunal anastomosis, perforation which has traditionally been dealt with by converting Billroth II gastro-jejunostomy reconstruction into Roux-en-Y has seen some changes lately. Recent studies have shown that this revision is not mandatory anymore and that omental patch repair has increasingly been shown to be sufficient (14).Furthermore, numerous studies done in the past 4 decades have shown that, general surgeons are not the only ones who utilize the omental patch. The omental pedicle flap has also been widely used by neurosurgeons, thoracic surgeons and in the plastic and reconstructive arena (15)(16)(17)(18).…”
Section: Omentoplasty In Perforated Peptic Ulcer Surgery: Is It Stillmentioning
confidence: 99%